Energy efficient copper electrowinning and direct deposition on carbon nanotube film from industrial wastewaters. (10th January 2019) - Hannula, Pyry-Mikko; Khalid, Muhammad Kamran; Janas, Dawid; Yliniemi, Kirsi; Lundström, Mari
Abstract: Heavy metal pollution is one of the most serious environmental issues of today. Removal of one common pollutant, copper, from synthetic wastewaters (containing copper, iron, sulfur and sodium) and complex authentic metallurgical plant wastewater (containing copper, iron, aluminum, zinc, nickel, arsenic, sulfur and lead among others) was studied by electrowinning. Due to the complexity and low concentration of these wastewater streams, energy efficient copper removal is challenging. The copper concentration in the investigated solutions varied from 100 to 428 ppm, while the iron concentration was an order of magnitude larger. Copper was recovered energy efficiently on glassy carbon from all investigated solutions that contained iron with a small specific energy consumption (1.5–2.5 kWh/kg Cu), depending on the solution composition and employed parameters. In the absence of iron, the specific energy consumption increased to ca. 3.5 kWh/kg Cu with the same parameters. The results indicate that the presence of iron in copper containing wastewater induces lower energy consumption during electrowinning, due to a decrease in cell voltage. Due to the low applied polarization the produced copper deposits from the authentic industrial wastewater were smooth and bright with no other metals as impurities, confirmed by energy-dispersive X-ray spectroscopy. Electrowinning was also applied on a carbon nanotube film as the working electrode to create carbon nanotube-copper composite structures of high purity directly from the industrial wastewater. These results highlight the energy efficient recovery of high purity copper from complex industrial wastewaters by electrowinning and furthermore, that the method may be used in producing high added value materials.